Exploring the influence of DNA methylation and single nucleotide polymorphisms of the Myostatin gene on growth traits in the hybrid grouper (Epinephelus fuscoguttatus (female) × Epinephelus polyphekadion (male)) - Cao, Liu; Ma, Jun; Chen, Pan; Hou, Xingrong; Yang, Ning; Lu, Yan; Huang, Hai (Frontiers in Genetics, 2024)
Investigations into the correlation between growth characteristics and DNA methylation levels, along with genetic variations, can provide fundamental insights to enhance growth performance in groupers. The Myostatin (mstn) gene plays a vital role in regulating skeletal muscle development and growth. This study scrutinized the DNA methylation levels of the mstn gene across hybrid groupers (Epinephelus fuscoguttatus (♀) × Epinephelus polyphekadion (♂)) and their parental species, to evaluate its impact on growth attributes in grouper fish. The findings revealed no significant differences in global DNA methylation levels within muscle tissue among the hybrid grouper and parents. However, 2 significant differences in DNA methylation sites were discovered between the hybrid grouper and E. polyphekadion at sites 824 and 1521 (located at exon 2 and intron 2, respectively), and between E.fuscoguttatus and E. polyphekadion at site 1521. These variations could potentially influence the mRNA expression of the mstn gene. Moreover, the nucleotide sequence of the mstn gene was directly sequenced in the hybrid grouper, exhibiting different growth performance to identify the single nucleotide polymorphisms (SNPs) of the mstn gene and explore their correlation with growth characteristics. The study identified that SNP g.1003 T > C in exon 2 of the mstn gene was significantly associated with various growth traits including body weight, total length, body length, head length, caudal peduncle height, and body height (p < 0.01).Specimens with the TT genotype at site 1003 demonstrated superior growth performance compared to those with the TC genotype.Furthermore, microstructural analyses of muscle tissue showed that the average area and diameter of muscle fibers in TT genotype individuals were significantly greater than those in TC genotype individuals.Therefore, this research provides robust evidence linking the DNA methylation level and polymorphisms of the mstn gene with growth traits, which could be beneficial for grouper breeding programs.